Written case formulations in the treatment of anorexia nervosa: Evidence for therapeutic benefits. Issue 9 (3rd June 2016) - Allen, Karina L.; O'Hara, Caitlin B.; Bartholdy, Savani; Renwick, Beth; Keyes, Alexandra; Lose, Anna; Kenyon, Martha; DeJong, Hannah; Broadbent, Hannah; Loomes, Rachel; McClelland, Jessica; Serpell, Lucy; et al.
ABSTRACT: Objective: Case formulation is a core component of many psychotherapies and formulation letters may provide an opportunity to enhance the therapeutic alliance and improve treatment outcomes. This study aimed to determine if formulation letters predict treatment satisfaction, session attendance, and symptom reductions in anorexia nervosa (AN). It was hypothesized that higher quality formulation letters would predict greater treatment satisfaction, a greater number of attended sessions, and greater improvement in eating disorder symptoms. Method: Patients were adult outpatients with AN ( n = 46) who received Maudsley Anorexia Nervosa Treatment for Adults (MANTRA) in the context of a clinical trial. A Case Formulation Rating Scheme was used to rate letters for adherence to the MANTRA model and use of a collaborative, reflective, affirming stance. Analyses included linear regression and mixed models. Results: Formulation letters that paid attention to the development of the AN predicted greater treatment acceptability ratings ( p = 0.002). More reflective and respectful letters predicted greater reductions in Eating Disorder Examination scores ( p = 0.003). Discussion: Results highlight the potential significance of a particular style of written formulation as part of treatment for AN. Future research should examine applicability to other psychiatric disorders. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:874–882)